Hybridization between an endangered freshwater fish and an introduced congeneric species and consequent genetic introgression - Hata, Hiroki (PLoS One, 2019)
Artificial transplantation of organisms and consequent invasive hybridization can lead to the extinction of native species. In Matsuyama, Japan, a native bitterling fish, Tanakia lanceolata, is known to form hybrids with another bitterling species, T. limbata, which was recently introduced from western Kyushu, Japan. These bitterlings spawn in the gills of two freshwater unionid species, Pronodularia japanensis and Nodularia douglasiae nipponensis, which have rapidly declined on the Matsuyama Plain in the past 30 years. To gauge the effect of invasive hybridization, we determined the genetic introgression between T. lanceolata and T. limbata and analyzed the morphology of these species and their hybrids to infer their niche overlap. We collected adult individuals of Tanakia spp. and genotyped them based on six microsatellite loci and mitochondrial cytochrome b sequences. We analyzed their meristic characters and body shapes by geometric morphometrics. We found that 10.9% of all individuals collected were hybrids. Whereas T. lanceolata were more densely distributed downstream and T. limbata were distributed upstream, their hybrids were widely distributed, covering the entire range of native T. lanceolata. The body height and anal fin length of T. limbata were greater than those of T. lanceolata, but their hybrids were highly morphologically variable, covering both parental morphs, and were widely distributed in the habitats of both parental species. Hybridization has occurred in both directions, but introduced T. limbata females and native T. lanceolata males are more likely to have crossed. This study shows that invasive hybridization with the introduced T. limbata is a potential threat to the native population of T. lanceolata via genetic introgression and replacement of its niche in streams.